2013
DOI: 10.1038/cddis.2013.283
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma protein regulates the crosstalk between autophagy and apoptosis, and favors glioblastoma resistance to etoposide

Abstract: Glioblastomas (GBMs) are devastating tumors of the central nervous system, with a poor prognosis of 1-year survival. This results from a high resistance of GBM tumor cells to current therapeutic options, including etoposide (VP-16). Understanding resistance mechanisms may thus open new therapeutic avenues. VP-16 is a topoisomerase inhibitor that causes replication fork stalling and, ultimately, the formation of DNA double-strand breaks and apoptotic cell death. Autophagy has been identified as a VP-16 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 55 publications
(90 reference statements)
1
53
1
Order By: Relevance
“…However, the role of pRb in cancer is not limited to cell cycle regulation and appears to be more complex. Indeed, pRb can be pro-apoptotic (Bowen et al, 1998;Hilgendorf et al, 2013;Ianari et al, 2009) or anti-apoptotic (Biasoli et al, 2013;Morgenbesser et al, 1994;Tsai et al, 1998), and the regulation of these opposite roles of pRb towards apoptosis remains poorly understood. The ability of pRb to induce apoptosis fits with its tumor suppressor function.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of pRb in cancer is not limited to cell cycle regulation and appears to be more complex. Indeed, pRb can be pro-apoptotic (Bowen et al, 1998;Hilgendorf et al, 2013;Ianari et al, 2009) or anti-apoptotic (Biasoli et al, 2013;Morgenbesser et al, 1994;Tsai et al, 1998), and the regulation of these opposite roles of pRb towards apoptosis remains poorly understood. The ability of pRb to induce apoptosis fits with its tumor suppressor function.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] While early myogenesis markers can be also expressed in proliferating cells, late differentiation markers, like myosin heavy chain (MHC), are induced only after cell cycle arrest. 15 The retinoblastoma protein (Rb) and cyclin D, plays a critical role in myoblasts cycle arrest; indeed myocytes and muscle cells lacking Rb fail to exit the cell cycle, [16][17][18][19][20][21][22][23][24][25][26] altering the late phases of skeletal myogenesis. In addition, the cyclin-dependent-kinase inhibitors p21…”
Section: Introductionmentioning
confidence: 99%
“…However, the autophagy induced by 5-FU can function either as a survival or as a death mechanism, apparently depending on the combination of genetic alterations in each cell [40], [41], [42]. We and others have previously shown that pRB regulates the completion of the autophagic process induced by anticancer drugs [13], [18], [21], [43].…”
Section: Discussionmentioning
confidence: 99%
“…The extracted protein (containing 15–40 μg of protein per sample) was diluted in sample buffer (10% SDS; 10 mM β-mercaptoethanol; 20% glycerol; 0.2 M Tris–HCl, pH 6.8; and 0.05% bromophenol blue) and electrophoresed in polyacrylamide gel (SDS-PAGE) according to our previous paper [13]. The antibodies used were polyclonal anti-RB 851 (1:5000, kindly given by Dr. Jean Y. J. Wang), phospho-RB at Ser807/811 (1:1000, Cell Signaling Technology), and anti-α-tubulin (1:10,000, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%